The Geopolitical Dimensions of Halayeb issue according to the Egyptian Political Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Egypt is considered one of the most important countries with a large area neighboring Sudan, and because of its area, it neighbors Sudan from the north with a border line whose length is (1273 km) and constitutes (16.5%) of the total length of Sudan’s borders with neighboring countries.Sudan has known its current borders since 1899 under the dual rule of Sudan (Anglo-Egyptian), which drew and worked with these borders until its exit upon Sudan’s independence in 1956, which stipulated maintaining the agreements that it had previously approved, especially regarding the borders. However, despite this, the Halayeb problem erupted as a difficult crisis between Egypt and Sudan that waved destroying the relationship in the region by escalating the crisis to undesirable consequences.This crisis believes that both Sudan and Egypt have not been able to represent an Arab Islamic hope and the Egyptian influence in Sudan is a required contribution on the part of the Sudanese themselves.